Factors influencing U.S. charitable giving during the Great Recession: Implications for nonprofit administration - Jerry D. Marx; Vernon B. Carter (Administrative Sciences, 2014)
The purpose of this study is to examine factors influencing U.S. charitable giving during the first full year of the Great Recession. Demand on the services of human service nonprofits typically escalates during periods of extreme economic downturn; thus donations to agencies serving the most vulnerable groups-the young, the old, and the frail-become increasingly important. The study sample consisted of 8690 U.S. respondents. Results indicate the growing importance of computer ownership and the continuing importance of combined purpose agencies in assisting the needy in hard times. Suggestions for both future research and nonprofit administrative practice regarding charitable giving are provided.
Keywords: 350; nonprofit administration; charitable giving; federated fundraising; international aid; online giving